Impact of government evaluation and accreditation processes on the research output of universities in developing countries: an X-ray of the young Ecuadorian academia - Gutiérrez, Gabriela; Yaguarema, Marcia; Ayala, Margarita; Zambrano R., Jimmy; Gutiérrez, Leo (Frontiers in Education, 2023)
Ecuador is a unique case study, where strict evaluation and accreditation processes have been recently established (i.e., early-2010s) mainly based on the experience of their peers and that of developed countries. Interestingly, the development of quality assurance indicators for research output received special attention. The current study systematically explored the research output of the Ecuadorian higher education institutions (HEIs) after only one decade of being subjected to multiple rigorous evaluation and accreditation processes. Peer-reviewed documents in the Scopus Database from 2006 to 2021 were statistically analyzed in terms of the number of documents produced (i.e., books, book chapters, journals, and conference proceedings), citations, H-index, quartiles, and impact factors (i.e., SRJ, SNIP, and Cite Score), at both country and single-university levels. The influence of the multiple evaluation processes and external factors (e.g., relaxation of regulations, COVID) on the research output trends were comprehensively and chronologically discussed. Accordingly, a statistical answer to the following research questions was attempted: where is the Ecuadorian research output currently standing after these evaluation and accreditation measures? Furthermore, where is it heading? This investigation would assist in creating and adjusting policies targeting sustainable research in HEIs in Ecuador and other countries in similar early research development.